Contribution to the assessment of patient safety culture in Algerian healthcare settings: The ASCO project - Fourar, Youcef-Oussama; Benhassine, Wissal; Boughaba, Assia; Djebabra, Mébarek (International Journal of Healthcare Management, 2022)
Background A positive Patient Safety Culture (PSC) is considered as the main barrier to adverse events (AEs) that affect healthcare quality and safety. Thus, the assessment of PSC became a priority for healthcare providers in order to identify problematic areas that need improvement actions. Method A cross sectional multi-center study was conducted to evaluate quantitatively PSC in 10 Algerian healthcare establishments (HEs) within the framework of the Algerian Observatory of Safety Culture (ASCO Project). The French version of the HSOPSC was used as a measurement tool where it was administered to participants (N = 1370) using convenience sampling. Results A total of 1118 respondents, all professional categories included, participated in this study. The response rate was estimated at 69% of the sample size (N = 1370). After statistical processing, 950 questionnaires were retained. Internal consistency was above 0.7 for all dimensions. Problematic PSC dimensions were identified, mainly ‘Non-punitive response to error’, ‘Staffing’ and ‘Communication openness’. Conclusions This article sheds light on the critical situation of PSC in the Algerian national health system. Quantitative findings were introduced in the framework of the Algerian Safety Culture Observatory project that will serve as a baseline for different stakeholders to guide long-term promotion actions.